Predicting Cyperus esculentus Biomass Using Tiller Number: A Comparative Analysis of Growth Models - Ya Ding; Yan Lu; Akash Tariq; Fanjiang Zeng; Yanju Gao; Jordi Sardans; Dhafer A. Al-Bakre; Josep Peñuelas (Agriculture)
Cyperus esculentus, a drought-resistant Cyperaceae with ecological and economic value (stems/leaves as feed, tubers as oil source), stabilizes arid soils through its extensive root system. Understanding its biomass allocation strategies is crucial for comprehending carbon storage in arid environments. The results showed that allometric models best described leaf biomass, while Gompertz and logistic models provided superior accuracy (evaluated using R2, p-value, AIC, RMSE, and RSS) for estimating root, tuber, and whole plant biomass. In our study, the equilibrium biomass showed that underground (74.29 g and 64.22 g) was superior to aboveground (63.63 g and 58.72 g); and the growth rate showed the same result, underground (0.112 and 0.055) surpassed aboveground (0.083 and 0.046). The initial inflection point (POI1 = 11) suggests that leaves are prioritized in acquiring limited resources to support growth. In conclusion, the tiller number is a reliable predictor for developing robust biomass models for C. esculentus. The Gompertz model is best for leaves, roots, and total biomass, while the logistic model is optimal for predicting tuber biomass in arid areas. The tiller number is a reliable predictor for developing robust biomass models for C. esculentus. The research findings have supplied useful insights into the growth modifications, production potential, and management experience gained from Cyperus esculentus plant agriculture.